Botryopera , Haeckel 1887 - Trubovitz, Sarah; Renaudie, Johan; Lazarus, David; Noble, Paula (Zenodo, 2022)
Genus Botryopera Haeckel, 1887, emend. Petrushevskaya, 1975 Type species: Botryopera cyrtoloba Haeckel, 1887 Description. No clear consensus exists for the definition of this genus, and even the family assignment has been debated in the literature. Here we loosely follow the description given by Petrushevskaya (1986), which states that Botryopera species are small in size, with a sub-cylindrical, elongated skeletal shape, a thorax that is ~45–75 microns wide and never broader than 100 microns, and have arches connecting the thorax to the cephalis that reach ~⅓ of the way up the cephalic segment. Here we add that species in this genus often exhibit an axobate, which is a character common to the lophophaenid genera Ceratocyrtis and Antarctissa, but is otherwise not widely observed in this family. Botryopera species also tend to have a cephalis that is heavier and better developed than the thorax. Remarks. Haeckel (1887) first described the genus Botryopera as one of two genera in the family Cannobotryida (Haeckel, 1881). He described Cannobotrys as the genus with porous tubes on the cephalis (a clear indication that these taxa should belong to the family Cannobotryidae ), and Botryopera as the genus without these tubes. Two species previously described by Ehrenberg (1844), Lithobotrys triloba and Lithobotrys quadriloba , were placed into Haeckel’s new genus Botryopera . However, Ehrenberg’s first published illustrations of Lithobotrys triloba in 1854c (pl. 19, fig. 55; pl. 22, figs. 30A–B) suggests that it is a lophophaenid due to its cephalis shape, lack of lobes or tubes, and pore structure. Haeckel (1887) states that the cephalis is trilobate, but there appears to be some confusion, as it is the thorax, not the cephalis, that has three lobes in this species. Reexamination and photo documentation of Ehrenberg’s collections by Suzuki et al. 2009 clearly indicates that the species Lithobotrys triloba Ehrenberg, 1854c should belong to the family Lophophaenidae (Suzuki et al., 2009; pl. 20, figs. 3A–B, ...